A bovine pulmosphere model and multiomics reveal early host response signature in tuberculosis - Vinay Bhaskar; Rishi Kumar; Manas Ranjan Praharaj; Sripratyusha Gandham; Hemanta Kumar Maity; Uttam Sarkar; Bappaditya Dey (Communications Biology)
Abstract Early interactions between tubercle bacilli and lung cells are critical in tuberculosis (TB) pathogenesis. Conventional two-dimensional cell cultures fail to replicate the multicellular complexity of lungs. We introduce a three-dimensional pulmosphere model for Mycobacterium tuberculosis infection in bovine systems, demonstrating through comprehensive transcriptome and proteome analyses that these multicellular spheroids closely mimic lung cell diversity, interactions, and extracellular matrix (ECM) composition. Cell viability, hypoxia, and reactive oxygen species assessments over three weeks confirm the model’s suitability. To establish infection, we employed M. bovis BCG—an attenuated vaccine strain, and M. tuberculosis H37Rv—a laboratory adapted human clinical strain that is attenuated for cattle infection compared to M. bovis. Both infection upregulated key host pathways; however, M. tuberculosis induced distinct responses, including enhanced ECM receptors expression, neutrophil chemotaxis, interferon signaling, and RIG-1 signaling. A six genes/protein signature- IRF1, CCL5, CXCL8, CXCL10, SERPINE1, and CFB -emerges as an early host response marker to M. tuberculosis infection. Infection with virulent M. bovis and M. orygis revealed a shared upregulated gene signature across Mycobacterium tuberculosis complex species, but with pathogen-specific variations. This study presents a robust ex vivo bovine pulmosphere TB model with implications in biomarkers discovery, high-throughput drug screening, and TB control strategies.